A systematic review of technology adoption frameworks and their applications - Koul,Sahil (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2017)
The Technology Acceptance Model and the Theory of Planned Behavior have demonstrated pioneering research efforts within the research domain of innovation adoption concerning new technologies. This study consolidated an in-depth literature review of both theoretical frameworks, covering their roots and development over the years within the scholarly community. Also, we reviewed the applicability of these frameworks within the context of emerging technologies of the information age. After a thorough literature review, we concluded that both frameworks are widely used and applicable to various emerging technologies and continue to remain instrumental in the research domain of innovation adoption.